Distributed energy resources integration in single-phase microgrids: An application of IDA-PBC and PI-PBC approaches (2019)
This paper presents a unified Hamiltonian formulation for controlling distributed energy resources (DERs)in ac single-phase microgrids (SP-MGs)via proportional-integral passivity-based control (PI-PBC), and interconnection and damping assignment passivity-based control (IDA-PBC). The proposed Hamiltonian formulation allows us to consider both pulse-width modulated voltage source converters (PWM-VSC)and pulse-width modulated current source converters (PWM-CSC)under a unified model. Renewable generation and supercapacitor energy storage systems are integrated via PWM-VSC technologies, while superconducting coils are integrated through PWM-CSC technologies. IDA-PBC and PI-PBC theories enable us to design control strategies begin that consider Lyapunov's stability theory combined with the well-known advantages of proportional and integral control actions. Our simulation's results corroborate the applicability of the proposed control approaches under stability paradigm. MATLAB/Simulink is employed for computational implementations via begin the SimPowerSystems toolbox. © 2019 Elsevier Ltd